THE RETENTION OF PVY IN THE STYLET OF MYZUS PERSICAE SULZ. AFTER THE APPLICATION OF MINERAL OIL ON POTATO PLANTS - Wróbel, Sławomir (Plant Breeding and Seed Science, 2009)
An important element of epidemiological studies is the understanding of PVY retention, that is to say, the time of the infectious virus remaining in the aphid’s stylet, after it is contracted by the aphid from an infected plant. The purpose of the research was to establish PVY retention in the stylet of Myzus persicae after using mineral oil for potato plant protection...